Differential dermal expression of CCL17 and CCL18 in tuberculoid and lepromatous leprosy. - William R Berrington; Chhatra B Kunwar; Kapil Neupane; Susan J F van den Eeden; James C Vary; Glenna J Peterson; Richard D Wells; Annemieke Geluk; Deanna A Hagge; Thomas R Hawn (Public Library of Science (PLoS), 2014)
Leprosy is characterized by polar clinical, histologic and immunological presentations. Previous immunologic studies of leprosy polarity were limited by the repertoire of cytokines known at the time.We used a candidate gene approach to measure mRNA levels in skin biopsies from leprosy lesions. mRNA from 24 chemokines and cytokines, and 6 immune cell type markers were measured from 85 Nepalese leprosy subjects. Selected findings were confirmed with immunohistochemistry.Expression of three soluble mediators (CCL18, CCL17 and IL-10) and one macrophage cell type marker (CD14) was significantly elevated in lepromatous (CCL18, IL-10 and CD14) or tuberculoid (CCL17) lesions. Higher CCL18 protein expression by immunohistochemistry and a trend in increased serum CCL18 in lepromatous lesions was observed. No cytokines were associated with erythema nodosum leprosum or Type I reversal reaction following multiple comparison correction. Hierarchical clustering suggested that CCL18 was correlated with cell markers CD209 and CD14, while neither CCL17 nor CCL18 were highly correlated with classical TH1 and TH2 cytokines.Our findings suggest that CCL17 and CCL18 dermal expression is associated with leprosy polarity.